Effects of uphill high-intensity interval exercise on muscle damage and exercise performance during recovery - Fares, R.; Rodríguez, M. Á.; Kairouz, K.; Vicente-Rodríguez, G.; Olmedillas, H. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Active recovery is believed to offer positive benefits related to exercise by improving recovery and potentially managing several symptoms following strenuous exercise. The current study aimed to verify the effects of a session of low-volume and uphill high-intensity interval exercise on muscle soreness and exercise performance within the recovery period after an exercise-induced muscle damage protocol. METHODS: Thirty-one young physically active subjects completed two identical test sessions following an exercise-induced muscle damage protocol, separated by a three-week period, in which they performed uphill high-intensity interval exercise or a passive recovery. The uphill high-intensity interval exercise consisted of four bouts of 30 seconds at maximum velocity, interspersed by 4 minutes of passive rest on an uphill treadmill. Rating of perceived exertion, muscle soreness, serum concentration of Creatine Kinase, muscle circumference, countermovement jump, sprint time, and 1 repetition maximum strength of quadriceps femoris were measured. The assessments were made for four consecutive days, before the exercise-induced muscle damage protocol and 24, 48, and 72 hours afterwards. RESULTS: A significant effect of time was found for all the outcome measures, but there were no significant differences between groups either in pain perception, muscle damage variables, nor in performance outcome measures at any point of time (P>0.05). CONCLUSIONS: Uphill high-intensity interval exercise performed after an exercise-induced muscle damage protocol does not exacerbate muscle soreness or worsens exercise performance in comparison with passive recovery.